2012
DOI: 10.5296/ijld.v2i4.2077
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Organizational Commitment as the Outcome of Job Satisfaction: A Study of Banking Sector of Pakistan

Abstract: This study aims to elaborate the role of job satisfaction in committing employees with organization. This study tested the effect of both components of job satisfaction (intrinsic and extrinsic) on organizational commitment in banking sector of Pakistan. Data was gathered from employees working in banks of Pakistan. The study has used descriptive statistics (mean and standard deviation) to identify sample characteristics and inferential statistics (multiple linear regression) to find out the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Thus far, results are in line with proposed hypotheses which mean H1 and H2 were supported. This report endorses previous studies that concluded intrinsic and extrinsic satisfaction had significant and positive impact on organizational commitment (eg [84]; [85]; [86]; [87]). It is indicated by this study that teachers become committed with their job when they are satisfied with both intrinsic and extrinsic rewards.…”
Section: Correlation Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Thus far, results are in line with proposed hypotheses which mean H1 and H2 were supported. This report endorses previous studies that concluded intrinsic and extrinsic satisfaction had significant and positive impact on organizational commitment (eg [84]; [85]; [86]; [87]). It is indicated by this study that teachers become committed with their job when they are satisfied with both intrinsic and extrinsic rewards.…”
Section: Correlation Resultssupporting
confidence: 76%
“…However, [47] suggested that all elements of job satisfaction (extrinsic, intrinsic and general satisfaction) had been found to significantly relate to organizational commitment. Again, [48] found significant and positive effect of both components of job satisfaction on organizational commitment. In another study, [49] Intrinsic job satisfaction, extrinsic job satisfaction, and overall job satisfaction were found to be significantly and highly related with organizational commitment, an indication that promoting job satisfaction elements (eg intrinsic, extrinsic and general satisfaction) improves employees" commitment to the organization.…”
Section: Intrinsic and Extrinsic Satisfactionmentioning
confidence: 81%
See 1 more Smart Citation
“…Job agreement is the most investigated variables in trade/ managerial psychology and is also one of the major factors that influence a worker practice at place of work. Job agreement able to be clear editors of a worker's physical and emotional job satisfaction as an amenable stimulating government ensuing from the evaluation of one's job practice (Hashmi & Naqvi, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kobasa and Antrosrusky (1998) have additionally affirmed the huge relationship between occupational stress and occupational commitment. According to Hashmi and Naqvi (2012) turnover of banks in the earlier years was at its peak but it is the low organizational commitment that banking sectors had to face that drove down the profits.…”
Section: Introductionmentioning
confidence: 99%